2022
DOI: 10.1111/php.13656
|View full text |Cite
|
Sign up to set email alerts
|

No Evidence of Induced Skin Cancer or Other Skin Abnormalities after Long‐Term (66 week) Chronic Exposure to 222‐nm Far‐UVC Radiation

Abstract: Far-UVC radiation, typically defined as 200-235 nm, has similar or greater anti-microbial efficacy compared to conventional 254-nm germicidal radiation. In addition, biophysical considerations of the interaction of far-UVC with tissue, as well as multiple short-term safety studies in animal models and humans, suggest that far-UVC exposure may be safe for skin and eye tissue.Nevertheless, the potential for skin cancer after chronic long-term exposure to far-UVC has not been studied. Here, we assessed far-UVC in… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
26
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(26 citation statements)
references
References 51 publications
0
26
0
Order By: Relevance
“…The use of far-UVC irradiation is considered a promising solution for efficient and safe disinfection based on the limited results of recent studies. , , Although some studies ,, showed that far-UVC exposure is likely to be safe for human skin and eyes, more long-term evidence on the harmlessness of far-UVC exposure is needed. Currently, there are regulatory exposure limits for 222 nm far-UVC irradiation.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The use of far-UVC irradiation is considered a promising solution for efficient and safe disinfection based on the limited results of recent studies. , , Although some studies ,, showed that far-UVC exposure is likely to be safe for human skin and eyes, more long-term evidence on the harmlessness of far-UVC exposure is needed. Currently, there are regulatory exposure limits for 222 nm far-UVC irradiation.…”
Section: Resultsmentioning
confidence: 99%
“…Currently, there are regulatory exposure limits for 222 nm far-UVC irradiation. For example, ACGIH (American Conference of Governmental and Industrial Hygienists) 8 h threshold limit values for 222 nm far-UVC are around 160 mJ/cm 2 for the eyes and 480 mJ/cm 2 for skin, which are much higher than the limit for 254 nm UV (6 mJ/cm 2 ). ,, However, the health issues related to exposure to 222 nm far-UVC are not concerns for in-duct or in-channel applications.…”
Section: Resultsmentioning
confidence: 99%
“…On the safety side, Brenner and colleagues reported in May that they had exposed hairless mice to the radiation for 66 weeks without detecting any skin cancer 7 . Their upcoming research will focus on the risk to the eyes, and further investigate the mechanisms of how 222 nm radiation damages pathogens.…”
Section: Riding Shorter Wavesmentioning
confidence: 99%
“…However, almost 20 years ago, Sosnin et al [ 6 ] found that there is short-wavelength UVC radiation, which damages eukaryotic cells less than prokaryotic cells. Meanwhile, it has been found that human skin tolerates UV radiation in the so-called far-UVC range of about 200–230 nm relatively well [ 7 , 8 , 9 , 10 , 11 , 12 , 13 ]. This radiation is almost completely absorbed in the stratum corneum and does not reach deeper skin layers.…”
Section: Introductionmentioning
confidence: 99%